PISA va TIMSS xalqaro tadqiqotlari kontekstida fizika o‘qituvchilarini tayyorlashning zamonaviy tendensiyalari - Isakova, М.I (SCIENCE and SOCIETY, 2026)
The article examines modern trends in the training of physics teachers in the context of international comparative studies such as PISA and TIMSS. Special attention is paid to analyzing the requirements for teachers’ professional competencies in the context of globalization of education and digital transformation. The article presents examples of the experience of countries that have achieved high results in international rankings.
Keywords: physics teacher training; international studies; pisa; timss; pedagogical innovations; functional literacy; competency-based approach; digitalization of education